A Pilot Randomized Controlled Trial of Virtual Reality Distraction to Reduce Procedural Pain During Subcutaneous Port Access in Children and Adolescents With Cancer. Issue 3 (30th March 2022) - Hundert, Amos S.; Birnie, Kathryn A.; Abla, Oussama; Positano, Karyn; Cassiani, Celia; Lloyd, Sarah; Tiessen, Petra Hroch; Lalloo, Chitra; Jibb, Lindsay A.; Stinson, Jennifer
Abstract : Objectives: We aimed to determine the feasibility of virtual reality (VR) distraction for children with cancer undergoing subcutaneous port (SCP) access. We also aimed to estimate preliminary treatment effects of VR compared with an active distraction control (iPad). Materials and Methods: A single-site pilot randomized controlled trial comparing VR to iPad distraction was conducted. Eligible children and adolescents were aged 8 to 18 years undergoing treatment for cancer with upcoming SCP needle insertions. Intervention acceptability was evaluated by child, parent, and nurse self-report. Preliminary effectiveness outcomes included child-reported pain intensity, distress, and fear. Preliminary effectiveness was determined using logistic regression models with outcomes compared between groups using preprocedure scores as covariates. Results: Twenty participants (mean age 12 y) were randomized to each group. The most common diagnosis was acute lymphocytic leukemia (n=23, 58%). Most eligible children and adolescents (62%) participated, and 1 withdrew after randomization to the iPad group. Nurses, parents, and children reported the interventions in both groups to be acceptable, with the VR participants reporting significantly higher immersion in the distraction environment ( P =0.0318). Although not statistically significant, more VR group participants indicated no pain (65% vs. 45%) and no distress (80% vs. 47%) during the procedure compared with the iPad group. Fear was similar across groups, with ~60% of the sample indicating no fear. Discussion: VR was feasible and acceptable to implement as an intervention during SCP access. Preliminary effectiveness results indicate that VR may reduce distress and distress compared with iPad distraction. These data will inform design of a future full-scale randomized controlled trial.